The inter – Test variability of growth hormone stimulation tests and factors affecting this variability. (December 2020) - Dori, Eyal Ben; Avnon Ziv, Carmit; Auerbach, Adi; Greenberg, Yael; Zaken, Hagit; Levy-Khademi, Floris
Abstract: Objective: To evaluate the variability of growth hormone stimulation tests results and factors affecting it in short children suspected of having growth hormone deficiency. Design: The cohort included patients with short stature suspected of having growth hormone deficiency, and who underwent a second stimulation test, after the first stimulation test was positive. Testing was done at a single center from May 2014 to October 2017. Patients' weight, height, age, sex, stimulating agents and test results were recorded. Results: The study population comprised 200 patients, 108 males and 92 females, average age 9.2 years (2.2–16.6 years). The average peak growth hormone was 5.2 μg/L and 7.8 μg/L in the first and second tests respectively and the concordance rate was 56.5%. The probability of a second positive test was increased if the peak growth hormone level in the first test was below 5 μg/L. In the second test, Clonidine and Glucagon led to higher peak growth levels than Arginine with averages of 9.02, 9.97 and 6.88 μg/L respectively. Younger children and children with higher BMI SDS only had lower peaks of growth hormone in the second test. The effect of height SDS on peak growth hormone levels was equivocal. Conclusion: The reproducibility rate of GH simulation tests in our study was low. A few factors may affect the peak levels of growth hormone in the second test, the most prominent being the peak of growth hormone in the first test. Highlights: Growth hormone stimulation tests have a high inter-test variability. Low peak GH in the first stimulation test reduces the inter-test variability. Effects of BMI SDS and height SDS on peak growth hormone levels in stimulation test were equivocal.